Social and Biological Correlates of Wild Meat Consumption and Trade by Rural Communities in the Jutaí River Basin, Central Amazonia - El Bizri, H.R.; Morcatty, T.Q.; Ferreira, J.C.; Mayor, P.; Vasconcelos Neto, C.F.A.; Valsecchi, J.; Nijman, V.; Fa, J.E. (SAGE Publications, 2020)
Wild animals are an important source of food and income throughout the Amazon basin, particularly for forest-dependent communities living in the more remote regions. Through interviews in 51 households within 16 communities in the Jutaí River Extractive Reserve, Amazonas, Brazil, we determined animal taxa consumed and frequency of wild meat consumption, as well as patterns of wild meat trade. We then investigated the influence of social and biological factors on wild meat consumption and trade. People declared consuming wild meat on an average of 3.2 ± 2.8 days/month/household, amounting to 198.85 kg/month consumed by all sampled households. The vast majority of respondents got wild meat by hunting themselves or it was given to them by their neighbors. The most consumed taxa were paca ( Cuniculus paca) and collared peccary ( Pecari tajacu). Approximately two-thirds of respondents declared selling wild meat; meat destined for urban markets was more expensive and was primarily sold from houses of relatives living in the city. Wild meat consumption was determined by taste preferences, while prices were related to the body mass of the taxa concerned. Frequency of wild meat consumption and the probability of selling wild meat were positively associated with the number of hunters in the household. We highlight the importance of wild meat for remote communities, and, importantly, the prominent links these communities have with urban markets. These findings are useful in developing strategies to ensure the sustainable use of wildlife in the Amazon.